Kilka uwag na temat wpływu zmian otoczenia prawnego na gospodarkę finansową zakładów ubezpieczeń w Polsce - Lisowski, Jacek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
Regulatory environment is one of the key factors influencing financial management of insurance companies in Poland. Changes in legal regulations and supervision practice have significant importance. Simultaneous changes, especially concerning accounting standards, capital requirements and consumer protection can cause serious problems for insurance companies. Only companies that observe those changes and take preemptive measures will be able to keep up. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 370-380